Essential fungal genetics - Moore, D. (David), 1942-; Frazer, LilyAnn Novak (New York, NY : Springer New York, 2002)
Most genetics textbooks deal adequately with plant and animal genetics, but tend to neglect fungi except for two areas. Firstly, the ascus segregations which, in the 1960s, contributed so much to developing an understanding of the mechanism of recombination and secondly, the contribution that work on yeast (as a model eukaryote) is currently making to understanding cell cycle control and its genetic regulation. Consequently, most introductory genetics texts will leave the reader/student with the impression that fungi are of use when peculiarities of their structure or life style suit them to particular experimental approaches, but are not worth mentioning otherwise. The authors have produced a book that will compensate for this imbalance. This book discusses the genetics of fungi, or mycology, in a way that is attractive and challenging, succinct yet comprehensive, sensitive to commercial and applied aspects, yet also theoretical, dealing with their genetics from molecules to individuals to population. This short text will be an ideal supplement to the established basic textbooks in genetics or can be used as the sole text for an advanced course devoted to fungal genetics.
Why Study the Genomes of Fungi? -- Genome Interactions -- Wild Types and Mutants -- Segregation Genetics: The Indirect Approach -- Recombination Analysis -- Mechanisms of Recombination -- The Physical Genotype -- Genes to Genomics: Mapping the Fungal Genome -- Systematics, Phylogeny, and Evolution -- The Genetics of Fungal Differentiation and Morphogenesis.
Elektronická reprodukce.
Keywords: houby; genetika rostlin; cytologie; genomika; fyziologie rostlin; mushrooms; plant genetics; cytology; genomics; plant physiology; e-knihy online; e-books online